Nine generations of a family with autosomal dominant retinitis pigmentosa and evidence of variable expressivity from census records. Issue 12 (December 1992) - Jay, M; Bird, A C; Moore, A N; Jay, B
Abstract : We present a nine generation family with autosomal dominant retinitis pigmentosa (ADRP). Evidence of blindness in the early generations, as obtained from census returns and clinical records, and examination of current patients show variable expressivity with a spectrum which ranges from asymptomatic in late life to blindness in the third decade of life. The family is not linked to any of the chromosomal locations so far described in ADRP and further illustrates the heterogeneity of the disorder.